Model Numeris Analisis Kinerja Simpang Bersinyal Berdasarkan MKJI 1997 - Muhammad Shiddiq Firman Abdullah; Adiman, Edi Yusuf Adiman; Mudjiatko; Yogi, Muhammad Rilly Aka (Jurnal Teknologi dan Rekayasa Sipil, 2025)
A numerical model of signalized intersection performance analysis based on the Highway Capacity Manual of Indonesian 1997 (MKJI 1997) is required to calculate the performance of signalized intersections in the effective and efficient manner. The modeling is formed by algorithmising the process of calculating the performance of signalized intersections based on MKJI 1997. The issue that affects the making of this model is the difference in the results of calculating the performance of the intersection using the KAJI application with manual calculations. This is caused by differences in each parameter which results in significant differences in results. Methods used to create a signalized intersection performance analysis program are validating three cases in MKJI 1997 and simulating two cases of previous research. The results of the validation of the numerical model that has been made against the three cases of MKJI 1997 obtained a delay value with an average percentage error of 1.26%. While the simulation results of two previous research cases obtained a delay value with an average percentage error of 2.74%. These results show that the average percentage error obtained is <10%, so the results of calculations using the program are categorized as very good.